Observer independent analysis of cerebral glucose metabolism in patients with chronic fatigue syndrome. Issue 7 (1st July 2003) - Siessmeier, T; Nix, W A; Hardt, J; Schreckenberger, M; Egle, U T; Bartenstein, P
Abstract : Objectives: To evaluate cerebral glucose metabolism, assessed by 18-fluorodeoxyglucose positron emission tomography (FDG-PET), in patients with chronic fatigue syndrome (CFS), using an observer independent analytical approach; and to characterise any observed alterations by correlating them with neuropsychological deficits. Methods: 26 patients (13 female, 13 male) were examined. They all fulfilled the CDC diagnostic criteria for CFS. Their ages ranged from 26 to 61 years (mean (SD) age, 43 (9.3) years). They underwent extensive psychometric testing including the hospital anxiety and depression scale (HADS) and the short form 36 item health questionnaire (SF-36). Brain FDG-PET was done in all the subjects. After stereotactic normalisation, single subject comparisons with an age and sex matched normal database (n = 18) and a group comparison between the patients and normal controls were undertaken, along with additional correlation analyses between brain metabolism and psychometric test scores. Results: 12 of the 26 patients showed no significant decrease in FDG uptake compared with the controls. Of the remaining 14, 12 showed hypometabolism bilaterally in the cingulate gyrus and the adjacent mesial cortical areas. Five of these 12 patients also had decreased metabolism in the orbitofrontal cortex. The two remaining patients had hypometabolism in the cuneus/praecuneus. Correlation analyses showed significant correlations between some test scores (anxiety, depression, health related quality of life) but not fatigue and regional reductions in glucose metabolism. Conclusions: Although abnormalities in FDG-PET were only detectable in approximately half the CFS patients examined, and no specific pattern for CFS could be identified, PET may provide valuable information in helping to separate CFS patients into subpopulations with and without apparent alterations in the central nervous system.